Pelatihan Digital Marketing Pada Umkm - Trisnawati Trisnawati; Riska Riska (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Currently, the marketing process for MSME products is still mostly done conventionally, even though some already use e-commerce platforms. So the process of marketing MSME products in Sukabumi City has not been organized. To further expose MSMEs in Sukabumi City, a special container is needed that can be used for marketing, promotion, sales, training, and information media processes. The method used to overcome these problems is the University of Muhammadiyah Sukabumi in collaboration with SEA (Sukabumi EntrepreneurAssociation) through Lecturers and Students in the Kedaireka Matching Fund Program with the theme "Digital Stalls as a Marketing Platform for MSMEs Sukabumi". One way to improve income MSMEs is by increasing product quality and also opening up marketing opportunities through distribution networks and accelerating digital marketing. So there is a need for training related to improving skills in terms of integrated marketing and the use of social media through digital marketing.